2004
DOI: 10.1152/ajpheart.00162.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adult rat cardiomyocytes exhibit capacitative calcium entry

Abstract: review. J. Bioenerg. Biomembr. 35:533-575. 15. Freichel, M., et al. 1999. Store-operated cation channels in the heart and cells of the cardiovascu-lar system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 39 publications
7
88
1
1
Order By: Relevance
“…However, in 2002 this laboratory (38) and Uehara and colleagues (122) demonstrated that Ca 2ϩ store depletion in neonatal and embryonic cardiomyocytes, respectively, resulted in a robust and persistent influx of extracellular Ca 2ϩ that was blocked by SOC inhibitors but not inhibitors of either L-type Ca 2ϩ channels (LTCC) or Na ϩ /Ca 2ϩ exchangers (NCX). We first reported the presence of SOCE in adult cardiomyocytes in 2004 using the combination of thapsigargin and the IP 3 -generating agonist ANG II (39). Using a differential dye-loading protocol to measure both ER/SR and cytosolic Ca 2ϩ levels, we observed a significant increase in cytosolic Ca 2ϩ concomitant with an immediate drop in store Ca 2ϩ levels, consistent with the activation of SOCE (39).…”
Section: Orai1/trpcmentioning
confidence: 65%
“…However, in 2002 this laboratory (38) and Uehara and colleagues (122) demonstrated that Ca 2ϩ store depletion in neonatal and embryonic cardiomyocytes, respectively, resulted in a robust and persistent influx of extracellular Ca 2ϩ that was blocked by SOC inhibitors but not inhibitors of either L-type Ca 2ϩ channels (LTCC) or Na ϩ /Ca 2ϩ exchangers (NCX). We first reported the presence of SOCE in adult cardiomyocytes in 2004 using the combination of thapsigargin and the IP 3 -generating agonist ANG II (39). Using a differential dye-loading protocol to measure both ER/SR and cytosolic Ca 2ϩ levels, we observed a significant increase in cytosolic Ca 2ϩ concomitant with an immediate drop in store Ca 2ϩ levels, consistent with the activation of SOCE (39).…”
Section: Orai1/trpcmentioning
confidence: 65%
“…First described in nonexcitable cells, CCE has now been shown to coexist with L-type channels in smooth and skeletal muscle cells (17,35) and in both neonatal and adult cardiomyocytes (12,13,31). The TRPC protein family has been a prime candidate for CCE channel proteins (14) and TRPC1, -3, -4, -5, and -6 have all been identified in rat and mouse hearts (14,28,30).…”
Section: Discussionmentioning
confidence: 99%
“…CCE or store-operated calcium, which was first described in nonexcitable cells (34), refers to the influx of Ca 2ϩ through plasma membrane calcium channels, activated in response to depletion of calcium in the endo/sarcoplasmic reticulum. We have demonstrated that in cardiomyocytes, Ca 2ϩ entry via the CCE-mediated pathway is clearly distinct from both L-type voltage-gated channels and the reverse mode of Na ϩ /Ca 2ϩ exchanger (12,13).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Angiotensin II, an IP 3 -generating agonist, is a potent stimulator of cardiomyocyte hypertrophy that can elevate cytoplasmic Ca 2+ during vasoconstriction, increased blood pressure, and hemodynamic stress. A number of studies have demonstrated that angiotensin II treatment leads to an increase in basal Ca 2+ levels in adult and neonatal cardiomyocytes (Kem et al 1991;Shao et al 1998;Hunton et al 2004), with sustained exposure affecting numerous cellular pathways (Meldrum et al 1996;Liu et al 2004b;Zhang et al 2004) and eventually resulting in cell death (Goldenberg et al 2001;Kajstura et al 1997). Elevating UDP-GlcNAc and O-GlcNAc levels through treatment with glucosamine or the O-GlcNAcase inhibitor PUGNAc attenuates angiotensin IIinduced CCE during I/R injury (Nagy et al 2006).…”
Section: Calcium Homeostasismentioning
confidence: 99%